Encyclopedia of Information Science and Technology, Fourth Edition 2018
DOI: 10.4018/978-1-5225-2255-3.ch630
|View full text |Cite
|
Sign up to set email alerts
|

New Faces of Digital Divide and How to Bridge It

Abstract: The chapter aims to explore, through the lenses of digital divide, what are challenges to alleviating socio-economic and intellectual limitations for prosperity of each individual. Cutting-edge research is reviewed to discuss in what way new technologies and access to them really help to develop citizens who are able to contribute in creative and democratic ways to society. While much effort has been done, in the past decade, to bridge the digital divide, by resolving access issues and usage issues, the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Whether from a tablet device or through Internet connection, access to resources allows students to increase their hours of connectivity. This finding is in accordance with other investigations, in which it is shown that access to digital resources is a determining factor in the development of digital competence [44][45][46][47]. In fact, Italian students who can connect to the Internet anywhere because they have this service on their mobile phones also reach a higher level of competence.…”
Section: Discussionsupporting
confidence: 92%
“…Whether from a tablet device or through Internet connection, access to resources allows students to increase their hours of connectivity. This finding is in accordance with other investigations, in which it is shown that access to digital resources is a determining factor in the development of digital competence [44][45][46][47]. In fact, Italian students who can connect to the Internet anywhere because they have this service on their mobile phones also reach a higher level of competence.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the impact on students, it is apparent that a digital divide persists as differences were observed by sex, purchasing power (availability of internet at home, number of computers and tablets) and digital practices (age of first use of electronic devices). This finding corroborates previous studies, which confirm the persistence of the digital divide both before (Pérez-Escoda et al, 2016; Freiman et al, 2018) and after the pandemic (Ong, 2020; Lai and Widmar, 2021). Public educational institutions must take each pupil’s situation into consideration and attempt to compensate for differences in digital skill levels.…”
Section: Discussionsupporting
confidence: 93%
“…El sexo, la edad, el nivel educativo, si poseen o no Internet en casa, si dispusieron de ultraportátil en la escuela, el número de ordenadores y tablets que tienen en su propio entorno o la edad en la que se iniciaron en el uso de algunos dispositivos, son elementos que marcan diferencias en relación a las emociones en el uso de las TIC. De esta forma, las emociones vinculadas al uso de las TIC en el alumnado, se aso- Freiman, Martinovic & Robichaud, 2018;Pérez-Escoda, Castro-Zubizarreta & Fandos-Igado, 2016;Schroeder, 2018). En resumen, tal y como se ha reflejado en la revisión bibliográfica, las emociones desempeñan un papel fundamental en la adquisición de cualquier meta (Hernández-Chérrez & Tayo, 2017;Reid, Thomson & McGlade, 2016;Zhang & Liu, 2016).…”
Section: Discusión Y Conclusionesunclassified